Antibiotic Prescribing by Dentists and Geographic Variability in the Veterans Affairs (VA) Health System. (4th October 2017) - Acosta, Kaitlyn; Patel, Ursula C; Evans, Charlesnika; Wesolowski, Michael; Gibson, Gretchen; Jurasic, Marianne; Fitzpatrick, Margaret; Miskevics, Scott; Ramanathan, Swetha; Suda, Katie J
Abstract: Background: In the US, dentists prescribe 10% of outpatient antibiotics and are the top specialty prescriber. However, it is difficult to distinguish antibiotic prophylaxis vs. treatment because dentists generally code using procedure codes (CDT), rarely using diagnostic codes (ICD). In VA, dentists use CDT and ICD codes allowing for analyses of prescription (RX) indication. Therefore, the study purpose was to determine prescribing rates and indication for antibiotics prescribed by dentists. Methods: Cross-sectional study of 476, 451 patients with 1, 741, 708 visits in 205 VA dental clinics in 2013. Dentist RXs within 7 days of a dental visit were associated for ICD/CDT. The antibiotic indication (treatment vs. prophylaxis) was determined using RX days supply and dental visit ICD. SAS was used for all analyses; P ≤ 0.05 was significant. Results: In 2013, there were 119, 773 antibiotic RXs for 77, 305 patients for a visit-based prescribing rate of 68.8/1000 visits. The most common antibiotic was amoxicillin (64.3%), followed by clindamycin (19.6%). Less than 2% of RX were broad-spectrum agents. The mean duration was 7.81 ± 8.52 days; 35% were > 10 days. The majority (69.9%) of antibiotics were prescribed for prophylaxis, with 30.1% prescribed for treatment of an oral infection. There was geographic variability in prescribing ( P < 0.01) with the highest prescribing rate in the West (74.9/1000 visits) and the lowest in the Northeast (57.2/1000 visits). By state, Arkansas (100.7/1000 visits) and North Dakota (33.5/1000 visits) had the highest and lowest rates, respectively (Figure). As compared with other regions, dentists in the Northeast were more likely to prescribe broad-spectrum agents (RR = 1.80; 95% CI: 1.57-2.08), but less likely to prescribe clindamycin as compared with B-lactams (RR = 0.86; 95% CI: 0.82-0.90; P < 0.01 for all). Conclusion: This is the first US study to determine indications and prescribing rates of antibiotics prescribed by dentists. Antibiotic dental prescribing varies geographically and differs as compared with prescribing patterns of medical providers. Dentistry may provide a novel opportunity for future stewardship efforts. Disclosures: All authors: No reported disclosures.